2016
DOI: 10.1002/jbm.a.35834
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte preseeding leads to an increased implant bed vascularization of biphasic calcium phosphate bone substitutes via vessel maturation

Abstract: The present study analyzes the influence of the addition of monocytes to a biphasic bone substitute with two granule sizes (400-700 μm and 500-1000 μm). The majority of the added monocytes was detectable as mononuclear cells, while also low amounts of (chimeric) multinucleated giant cells (MNGCs) were found. No increase in the total number of MNGCs was established, but a significantly increased percent vascularization. Altogether, the results show that the added monocytes become involved in the tissue response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…For BBSMs, the tissue reaction is formed by the individual reactions towards each of the material compounds. Therefore, aspects such as biodegradation is based on the activity of phagocytes such as macrophages and BMGCs towards the individual compounds (10,12,17,(20)(21)(22)(23)(24)(25)(26). Hence, BBSMs initially induce an inflammatory tissue reaction similar to that of a pure β-TCP material, resulting in a high number of BMGCs and a high degradation rate, at later stages this is followed by a slower degradation rate correlated with lower BMGC numbers at a later, which can be compared to pure HA (17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For BBSMs, the tissue reaction is formed by the individual reactions towards each of the material compounds. Therefore, aspects such as biodegradation is based on the activity of phagocytes such as macrophages and BMGCs towards the individual compounds (10,12,17,(20)(21)(22)(23)(24)(25)(26). Hence, BBSMs initially induce an inflammatory tissue reaction similar to that of a pure β-TCP material, resulting in a high number of BMGCs and a high degradation rate, at later stages this is followed by a slower degradation rate correlated with lower BMGC numbers at a later, which can be compared to pure HA (17).…”
mentioning
confidence: 99%
“…It has also been revealed that BBSMs induce tissue reactions that may support the bone regeneration process (17,20,32). Thus, BBSMs have been shown to be favorable materials for bone tissue regeneration in different preclinical and clinical studies (10,12,17,20,21,23,24,(32)(33)(34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this aspect was not addressed in the present study, where it was only possible to speculate on the molecular patterns derived from the monocyte fraction within the transplanted BMC in the various processes involved in bone healing. The beneficial role of monocytes in revascularisation is demonstrated by Barbeck et al (2016). Monocytes lead to an increased implant bed vascularisation of biphasic calcium phosphate bone substitutes through vessel maturation, but the underlying mechanism is not addressed (Barbeck et al, 2016).…”
Section: Monocytes As Regenerative Cellsmentioning
confidence: 99%
“…The beneficial role of monocytes in revascularisation is demonstrated by Barbeck et al (2016). Monocytes lead to an increased implant bed vascularisation of biphasic calcium phosphate bone substitutes through vessel maturation, but the underlying mechanism is not addressed (Barbeck et al, 2016). Spiller et al (2014) show that both the inflammatory and anti-inflammatory macrophage subtypes are capable of supporting revascularisation, albeit through different modes of action.…”
Section: Monocytes As Regenerative Cellsmentioning
confidence: 99%